The Role of Parents in Developing Early Childhood Spiritual Intelligence in an Islamic Education-Based Family Environment - Nabilaa Faizatuz Zuhriyah (Sekolah Tinggi Agama Islam Kuningan (STAIKuningan), 2025)
This study aims to examine the role of parents in developing early childhood spiritual intelligence in an Islamic education-based family environment. This study used a qualitative approach with a descriptive design, involving 20 parents of young children in Muslim families. Data were collected through in-depth interviews, questionnaires and observation of religious education activities at home. The results showed that mothers have a dominant role in teaching daily prayers, prophet stories and basic worship procedures to their children. However, fathers' involvement in their children's religious education is still limited, with most fathers mostly modeling personal worship without being directly involved in religious teaching activities. The study also found that religious instruction conducted by parents has a positive effect on the development of children's spiritual intelligence, as seen in the children's progress in memorizing prayers and their improved behavior. The study suggests the importance of increasing fathers' involvement in children's religious instruction and encourages the development of programs that involve both parents in early childhood spiritual education.